Efficacy of Sodium Tetradecyl Sulphate for the Treatment of Venous Malformation of The Head and Neck - Akram, Komal; Uzair Bin Akhtar; Shoaib Younus; Omer Sefvan Janjua; Rubbab Zahra; Sana Babar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the efficacy of Sodium Tetradecyl Sulphate for the treatment of venous malformations of the head and neck region. Study Design: A prospective clinical study. Place and Duration of Study: Oral and Maxillofacial Surgery department of Sharif Medical and Dental College Lahore, Pakistan from Apr 2021- Apr 2022. Methodology: All the patients who met the inclusion criteria and were willing to take part in the study were enrolled. Pre-operative demographic data, clinical examination findings were noted in the specially designed proforma. The diagnosis was confirmed using doppler ultrasonography. 0.5-2ml of 3% STS was injected in the lesions transcutaneously or transmucosally depending on the location after aspiration and till blanching of the lesion occurred. Cases were followed up for 04 weeks and pre-op and post-op results were assessed independently by a consultant using the Achauer’s scale. Results: Total 22 patients were enrolled. Mean age in the study was 17+11.93 years. Male to female ratio was 1:2.1. Buccal mucosa and the tongue were the most common sites, involved in 7(31.8%) cases. Complete and partial resolution was obtained in 14(63.6%) 22 cases. There were no post op complaints in majority of the patients. Post op pain, ulceration and sloughing was reported by 2(9.1%) of the patients. Conclusion: The results of the study show that 3% STS was effective in reducing the size of the lesion to approximately 50% to the original size. Overall efficacy was found to be 63.6% with minimum morbidity and side effects.